Effects of radiological weapons - Liolios, T. E. (HNPS Advances in Nuclear Physics, 2019)
An investigation of radiological weapons effects is performed by employing computerized simulation methods and various mathematical models. The study covers all major DU ammunitions that are used in modern warfare and calculates the expected cancer mortality as a function of weapon and battle conditions. Moreover, various forms of crude radiological devices (the weapon of choice in an unconventional terroristic attack) are also studied in order to evaluate the results of such an attack during the Athens 2004 Olympic games.